2022
DOI: 10.3390/medicina58060771
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Intervention for Recurrent Aphthous Stomatitis: A Network Meta-Analysis

Abstract: Background and objectives: To compare the efficacy and safety of topical interventions used for recurrent aphthous stomatitis. Materials and Methods: This network meta-analysis was conducted in accordance with the PRISMA statement. We searched four electronic databases, PubMed, Web of Science (WOS), Cochrane Central Register of Controlled Trials and Embase, for randomized controlled trials reporting efficacy and safety data on topical interventions for recurrent aphthous stomatitis. We performed a quality eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…When there is a symptom of exacerbation, topical glucocorticoids (GCs) are the first-line drug for minor RAS. They are used for the local treatment through their anti-inflammatory and immunosuppressive effects [9,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…When there is a symptom of exacerbation, topical glucocorticoids (GCs) are the first-line drug for minor RAS. They are used for the local treatment through their anti-inflammatory and immunosuppressive effects [9,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…50,73 Several pharmacological treatments have been used to treat aphthous stomatitis, and topical corticosteroids are the most commonly used treatment (Box 1). 50,73,74 A recent network meta-analysis of 69 RCTs of 29 topical and local therapies for recurrent aphthous stomatitis that included 5272 patients reported that use of topical triamcinolone reduced recurrent ulcers (mean percentage reduction in pain score, 28.4% [95% CI, 10.4% to 46.8%]) and size of lesions (mean percentage reduction in size, 25.8% [95% CI 7.91% to 45.48%]) compared with placebo. 74 Laser therapy has also been used to alleviate symptoms and foster ulcer healing for recurrent aphthous stomatitis.…”
Section: Treatmentmentioning
confidence: 99%
“…50,73,74 A recent network meta-analysis of 69 RCTs of 29 topical and local therapies for recurrent aphthous stomatitis that included 5272 patients reported that use of topical triamcinolone reduced recurrent ulcers (mean percentage reduction in pain score, 28.4% [95% CI, 10.4% to 46.8%]) and size of lesions (mean percentage reduction in size, 25.8% [95% CI 7.91% to 45.48%]) compared with placebo. 74 Laser therapy has also been used to alleviate symptoms and foster ulcer healing for recurrent aphthous stomatitis. 50,[74][75][76][77] The aforementioned network meta-analysis reported that laser was superior to placebo in reducing recurrent aphthous stomatitis symptoms (mean percentage reduction, 32.2% [95% CI, 16.4% to 48.1%]).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations